Wetting of Ni-based amorphous and crystalline alloys by Sn and Sn-based solders. (August 2020) - Lin, Qiaoli; Ye, Changsheng; Sui, Ran
Abstract: Using wetting balance method, the wettability of Ni-based amorphous and crystalline alloys by Sn and Sn-based solders (Sn-0.7Cu, Sn-0.3Ag-0.7Cu, and eutectic SnPb ( E -SnPb, Sn63Pb37)) was evaluated at 290–310 °C. Among these solders, Sn shows the best wettability with amorphous alloy because of the strongest interfacial reactivity for oxide film removal, and E -SnPb shows the best wettability with crystalline alloy due to the minimum surface tension of E-SnPb solder. Generally, amorphous alloys have the better wettability. At least two factors caused this situation, i.e., the relatively larger surface energy of amorphous alloy and the volume shrinkage caused by the structural relaxation and the primary crystallization during wetting. In this study, the wetting mechanism actually is the deoxideation, which includes the reaction of Sn with NiO, and the mechanical removal of the oxide film. Highlights: Amorphous Ni-based alloys shows a better wettability than the crystalline one. Wetting was caused by the oxide film removal. Capillary infiltration caused by volume shrinkage accelerated oxide film removal.